Medical Therapy for Pediatric Vascular Anomalies - Margolin, Judith F.; Soni, Heather Mills; Pimpalwar, Sheena (Seminars in Plastic Surgery, 2014)
Vascular anomalies (VAs) comprise a large variety of individual diagnoses that in different phases of treatment require a diverse number of medical specialists to provide optimal care. Medical therapies include agents usually associated with cancer chemotherapy, such as vincristine, as well more immunomodulatory types of drugs, such as glucocorticoids and sirolimus. These immunomodulating drugs are being successfully applied in cases that are typically categorized as vascular tumors, including kaposiform hemangioendothelioma (KHE) and tufted angioma (TA), as well as some of the more invasive types of vascular malformations (i.e., microcystic lymphatic malformations and blue rubber bleb nevus syndrome (BRBNS). These therapies need to be combined with good supportive care, which often involves anticoagulation, antimicrobial prophylaxis, and comprehensive pain and symptom-relief strategies, as well as appropriate drug monitoring and management of side effects of medical treatment. The optimal care of these patients frequently involves close collaboration between surgeons, interventional and conventional radiologists, medical subspecialists, and nurses.
Keywords: vascular anomalies; chemotherapy; sirolimus; kaposiform hemangioendothelioma; tufted angioma; blue rubber bleb nevus syndrome